1995
DOI: 10.1002/jso.2930590109
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane fatty acid profile in patients with primary carcinoma of the gallbladder

Abstract: Erythrocyte fatty acids were determined in patients with gall stones and carcinoma of the gallbladder. Significantly low levels of myristic acid (P < 0.01) and stearic acid (P < 0.001) and significantly high levels of palmitoleic acid (P < 0.05) and oleic acid (P < 0.01) were observed in cancer patients. Arachidonic and linolenic acid were significantly high in gallstone patients, but there was no significant difference in the lauric acid and palmitic acid levels. Thus an altered lipid metabolism in cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…Although not much delta 9 desaturation was seen in the present study when compared to the results of our earlier study [11], however this may be due to less number of patients in our earlier study and high variance thus observed. We had earlier proposed a role of free radical mediated lipid peroxidation in gallbladder carcinogenesis, however, our attention was subsequently drawn to the relationship of lipid peroxidation product 4-hydroxynonenal (HNE) and electrolytes suggesting that increase in lipid peroxidation products was probably due to increased stasis rather than increased peroxidation [12].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Although not much delta 9 desaturation was seen in the present study when compared to the results of our earlier study [11], however this may be due to less number of patients in our earlier study and high variance thus observed. We had earlier proposed a role of free radical mediated lipid peroxidation in gallbladder carcinogenesis, however, our attention was subsequently drawn to the relationship of lipid peroxidation product 4-hydroxynonenal (HNE) and electrolytes suggesting that increase in lipid peroxidation products was probably due to increased stasis rather than increased peroxidation [12].…”
Section: Discussioncontrasting
confidence: 98%
“…Similar to the results of our earlier study [11], the present study too show a fall in concentration of arachidonic acid in patients with gallbladder cancer, compared to patients with cholelithiasis, however, absence of a normal control group preclude the exact interpretation of this observation. Although not much delta 9 desaturation was seen in the present study when compared to the results of our earlier study [11], however this may be due to less number of patients in our earlier study and high variance thus observed.…”
Section: Discussionsupporting
confidence: 91%
“…Role of allele specific mutations in pathogenesis of carcinoma gallbladder has also been reported[54]. Another report by Pandey et al[55] has shown higher frequency of carcinoma gallbladder in patients with A+ and AB+ blood groups to which the reason is still unknown.…”
Section: Etiological Factors For Gbc Pathogenesismentioning
confidence: 94%
“…Decreased level of stearic acid in red-cell membranes, as well as (Wood et al, 1985;Kelly et al, 1990;Persad et al, 1990;Pandey et al, 1995). In addition, a prospective study of survival of breast-cancer patients showed a strong negative association between risk of metastases and stearic-acid level in membrane phosphatidylcholine in the primary tumor (Bougnoux et al, 1992).…”
Section: Discussionmentioning
confidence: 99%